A TBC1D9-Rab29 axis controls homeostatic NF-κB signaling and selective IL-6 production in epithelial cells - Hu, Xin; Nozawa, Takashi; Minowa-Nozawa, Atsuko; Murase, Kazunori; Nakagawa, Ichiro (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundInterleukin-6 (IL-6) plays a crucial role in inflammation and immune defense; however, its intracellular trafficking and the mechanisms regulating its expression remain poorly understood.MethodsWe investigated epithelial cell responses to poly(dA:dT) stimulation and group A Streptococcus infection, using depletion and overexpression assays, NF-κB readouts, proteomics, co-immunoprecipitation, immunofluorescence imaging, and analysis of necrotizing soft tissue infection transcriptomes.ResultsTBC1D9, a Rab GTPase-activating protein, selectively regulates IL-6: its depletion reduced IL-6 mRNA and protein levels without broadly affecting other pro-inflammatory cytokines. TBC1D9 maintained basal p65 phosphorylation but was dispensable for stimulus-induced NF-κB activation, supporting the idea that homeostatic NF-κB signaling is necessary for constitutive IL-6 transcription. Proteomics identified Rab29 as a TBC1D9 partner; co-immunoprecipitation showed preferential interaction with GTP-dependent Rab29, and the two proteins co-localized following stimulation and infection. Rab29 overexpression inhibited NF-κB activation and IL-6 production, while Rab29 deficiency increased both, opposing TBC1D9’s effect. Necrotizing soft tissue infection patients’ datasets showed upregulation of TBC1D9 and IL-6-related pathways, revealing their clinical relevance.ConclusionThe TBC1D9–Rab29 axis connects GTPase signaling and membrane trafficking to specifically regulate IL-6 in epithelial cells, revealing a non-traditional mechanism for modulating inflammation and a potential target in IL-6-driven diseases.